The developmental role of the local community in achieving local development in light of the participatory approach with reference to the Algerian experience - Zeroual, Sihem (Journal of Human Sciences, 2022)
This study attempts to provide a scientific analysis of the relationship between the participatory approach and local development, by showing the advantages of involving informal actors such as associations that are active at the local level in the decision-making process, and participating in the planning and implementation of development programs and moving a way from the centralization of decision-making and its reflection on quality of life of the residents of those local communities, by clarifying the mechanisms and foundations of the participatory approach and its objectives especially those related to the development process, by highlighting its obstacles and ways to activate its performance with reference to the Algerian experience.